Hubungan ASI Eksklusif dengan Kejadian Infeksi Saluran Pernapasan Akut pada Balita di Sekitar Pembangkit Listrik Tenaga Uap Batubara Babelan, Bekasi Jawa Barat - Puji Amrih Lestari (Yayasan Pendidikan Medika Indonesia, 2021)
Background. ARI is a major cause of morbidity and mortality from infectious diseases worldwide. Exclusive breastfeeding is one of the factors that can affect the incidence of ARI in toddlers. The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of ARI in toddlers around the Babelan Coal Power Plant, Bekasi, West Java. Method. This type of research is analytic research with a cross sectional study design. The measured variables were the characteristics of toddlers, exclusive breastfeeding and the incidence of ARI in toddlers. The research population is children under five years old 0-59 months who live around the PLTU Coal Babelan with a sample of 100 toddlers. Data were analyzed by chi-square test and logistic regression. Results. The variables of gender, age and history of exclusive breastfeeding statistically showed no significant relationship to the incidence of ARI in children under five. The results of multivariate analysis showed that the variable history of exclusive breastfeeding was the most dominant variable of the three final modeling variables with OR = 6.44. Conclusion. A history of exclusive breastfeeding can be a risk factor for the occurrence of ARI in infants because exclusive breastfeeding for the first 6 months is protective for the development of respiratory tract infections in infants and as a reduction in the risk of respiratory tract infections being lower after those aged over 5 years.